Nuclear receptor Ftz-f1 promotes follicle maturation and ovulation partly via bHLH/PAS transcription factor Sim - Elizabeth M Knapp; Wei Li; Vijender Singh; Jianjun Sun (eLife, 2020)
The NR5A-family nuclear receptors are highly conserved and function within the somatic follicle cells of the ovary to regulate folliculogenesis and ovulation in mammals; however, their roles in Drosophila ovaries are largely unknown. Here, we discover that Ftz-f1, one of the NR5A nuclear receptors in Drosophila, is transiently induced in follicle cells in late stages of oogenesis via ecdysteroid signaling. Genetic disruption of Ftz-f1 expression prevents follicle cell differentiation into the final maturation stage, which leads to anovulation. In addition, we demonstrate that the bHLH/PAS transcription factor Single-minded (Sim) acts as a direct target of Ftz-f1 to promote follicle cell differentiation/maturation and that Ftz-f1’s role in regulating Sim expression and follicle cell differentiation can be replaced by its mouse homolog steroidogenic factor 1 (mSF-1). Our work provides new insight into the regulation of follicle maturation in Drosophila and the conserved role of NR5A nuclear receptors in regulating folliculogenesis and ovulation.